Dual Role of Inflammasome Adaptor ASC in Cancer - Protti, Maria Pia; De Monte, Lucia (Frontiers in Cell and Developmental Biology, 2020)
Apoptosis-associated Speck-like protein containing a CARD (caspase activation and recruitment domain) (ASC), also called PYCARD/TMS1, was originally discovered as a protein that forms aggregates, called specks, in human leukemia cells treated with chemotherapeutic agents. Its expression was found silenced by methylation in many human tumors preventing tumor cells from undergoing apoptosis, supporting its role as tumor suppressor. Subsequently, ASC was also identified as a central adaptor molecule of the inflammasome complex, which mediates the secretion of inflammatory cytokines (i.e., IL-1 and IL-18). Inflammatory cytokines have been shown to mediate tumor-promoting functions. Thus, in the context of cancer development and progression ASC may exert opposing functions, i.e., being either tumor-suppressor by inducing tumor cell apoptosis or tumor-promoting by favoring secretion of inflammatory cytokines by tumor cells and/or tumor infiltrating myeloid cells within the tumor microenvironment. Here we report and discuss this dual role of ASC by also considering the final contribution of each of its two main functions in several cancer types taking into consideration the correlation between ASC expression, clinical correlates and patients’ survival. ASC and inflammasome targeting strategies are being developed: however, before the use of such treatments in the clinical practice it will be fundamental to better dissect the role of ASC in different tumors in order to privilege or avoid their use in those tumors, in which ASC exerts an anti-tumor or pro-tumor function, respectively.